Evaluation of Drug use Patterns for Pain Management in Patients with Knee Osteoarthritis Undergoing Physiotherapy in a Tertiary Care Teaching Hospital - Khadka, Aanjan; Gautam, Madan; Thapa Magar, Mohit; Yadav, Ajay Kumar; Jaiswal, Riya; Lamichhane, Sharmila (Birat Journal of Health Sciences, 2025)
Introduction: Osteoarthritis is becoming more common, and there is no definitive treatment for it. Medications like opioids, non-steroidal anti-inflammatory drugs, and steroids are used to relieve the pain of osteoarthritis in addition to physiotherapy. The pattern of use of medications for osteoarthritis varies widely with the chance of inappropriate drug combinations. Objective: To assess the drug use patterns for pain management in patients with knee osteoarthritis undergoing physiotherapy in a tertiary level teaching hospital. Methodology: A descriptive cross-sectional study was conducted in patients with knee osteoarthritis attending Physiotherapy department, Nepalese Army Institute of Health Sciences after IRC approval (Reg. No.:724 dated Dec 2022 from January 2023 to December 2023. The prescription of 115 patients were included to determine the prescribing indicators laid down by World Health Organization. The data were analyzed using descriptive statistics. Results: This study found female preponderance in disease occurrence and the average age was 66.12±6.71 years. Bilateral knee osteoarthritis was common (75.65%). NSAIDs (94.78%) were the most commonly prescribed class of drugs. Combination of analgesic-NSAIDs/Opioids and gastro protective agents (59.13%) were mainly prescribed and the average number of drugs per prescription was found to be 2.23. Conclusion: The finding of this study revealed NSAIDs as commonly prescribed drug and the two drug combination regimens as most commonly preferred regimen in the treatment of osteoarthritis.